Asc-1 Transporter Regulation of Synaptic Activity via the Tonic Release of d-Serine in the Forebrain. (21st January 2016) - Sason, Hagit; Billard, Jean Marie; Smith, Garrick Paul; Safory, Hazem; Neame, Samah; Kaplan, Eitan; Rosenberg, Dina; Zubedat, Salman; Foltyn, Veronika N.; Christoffersen, Claus Tornby; Bundgaard, Christoffer; Thomsen, Christian; et al.
Abstract: d -Serine is a co-agonist of NMDA receptors (NMDARs) whose activity is potentially regulated by Asc-1 (SLC7A10), a transporter that displays high affinity for d -serine and glycine. Asc-1 operates as a facilitative transporter and as an antiporter, though the preferred direction of d -serine transport is uncertain. We developed a selective Asc-1 blocker, Lu AE00527, that blocks d -serine release mediated by all the transport modes of Asc-1 in primary cultures and neocortical slices. Furthermore, d -serine release is reduced in slices from Asc-1 knockout (KO) mice, indicating that d -serine efflux is the preferred direction of Asc-1. The selectivity of Lu AE00527 is assured by the lack of effect on slices from Asc-1-KO mice, and the lack of interaction with the co-agonist site of NMDARs. Moreover, in vivo injection of Lu AE00527 in P-glycoprotein-deficient mice recapitulates a hyperekplexia-like phenotype similar to that in Asc-1-KO mice. In slices, Lu AE00527 decreases the long-term potentiation at the Schaffer collateral-CA1 synapses, but does not affect the long-term depression. Lu AE00527 blocks NMDAR synaptic potentials when typical Asc-1 extracellular substrates are present, but it does not affect AMPAR transmission. Our data demonstrate that Asc-1 mediates tonic co-agonist release, which is required for optimal NMDAR activation and synaptic plasticity.